Two Notes on the Neo-Hittite Name Sahwi - Simon, Zsolt (Orientalia, 2024)
This article argues that Šaḫu-, the Urartian spelling of the Iron Age Luwian name Sahwi-, reflects a phonologically regular by-form, and Sahwi- is a theophoric name, based on the name of an Anatolian deity which is known from both the Hittite archives and Carian theophoric names.